PENGARUH FASILITAS FISIK TERHADAP KEPUTUSAN PEMBELIAN KAMAR TAMU DI THE AXANA HOTEL PADANG - Jabbar, Abdul (journal of residu, 2019)
The study and was initiated by the decline in occupancy rate the guest room in the period of 2016-2017. This study aims to : (1), knowing the physical in the Axana the Padang, (2), knowing the purchasing decision of the room at The Axana the Padang, and (3) Analyze the influence of the physical against the decision of the purchase of the guests at The Axana the Padang. This type of research is sort of descriptive set of quantitative. The maker of samples is purposive sampling as many as 88 people. The gathering data using the questionnaire based on " Likert that has proven its validity and reliability of a. The result of this research is : (1) The facility physical in the Axana the Padang from all indicators that have been determined, including the category of agree with a percentage of 67 % (2) The purchase in the Axana the Padang from all indicators that have been determined, including in the category of agree with a percentage of 52 %, and (3) The analysis showed, there is a significant influence between the physical against the decision of the purchase of the guests at The Axana the Padang, Fhitung 20.018 with a sig. 0,000<0, 5 (ha and h0 be rejected).